Experimental apparatus for investigating colonization, succession and related processes of rocky bottom epifauna. (15th January 2022) - Kuklinski, Piotr; Balazy, Piotr; Porter, Joanne; Loxton, Jennifer; Ronowicz, Marta; Sokołowski, Adam
Abstract: To fully understand what controls the structure of benthic assemblages, recognition of the factors that influence each step of their development is needed. This includes knowledge about crucial processes such as biota recruitment and succession. Complex, heterogeneous natural substrates occurring on the sea floor, such as rocks, boulders and biogenic substrata, are often difficult to replicate experimentally. Uniform artificial substrate in the form of plates, often referred to as settlement panels, mimic the natural hard substrata of the rocky bottom and provides uniform replication at a wider scale. This allows scientists to study recruitment and succession processes and also various other issues related to colonization in aquatic environments. In this paper, we present detailed instructions for the construction of a settlement panel apparatus that has been used successfully over multiple years to study epifaunal succession and colonization in shallow-water marine environments around the world; we also provide practical examples of such studies from temperate and polar areas. Highlights: To fully understand what controls the structure of benthic assemblages, recognition of the factors that influence each step of their development is needed. System allowing the successful investigation of the community processes of recruitment, succession and related processes is provided. Detailed instructions for the construction of a settlement panel apparatus is described. Practical examples apparatus usage in the past are presented.